Contextual dependency and overuse of estar in the acquisition of Spanish copula verbs. Issue 5 (October 2022) - Aveledo, Fraibet; Sanchez-Alonso, Sara; Piñango, Maria Mercedes
The delayed acquisition of Spanish ser and estar is generally understood as rooted in the cognitive demands imposed by the integration of semantic-pragmatic and world-knowledge factors associated with their lexical meanings. Here we ask (1) what is the nature of this language world-knowledge integration? and (2) what is the developmental trajectory including its age distribution? We examine Spanish copula production and comprehension in 142 children (age range: 4–12 years) and 26 adults. Using two tasks, sentence-choice (comprehension) and cued-production (production), we test the hypothesis that estar use is constrained by an ability to construe an alternative to the copula predication; an ability that develops with life experience. We test estar / ser use in two contexts: alternative-supporting, favoring estar use; and alternative-neutral, neutral regarding estar use, and possibly favoring ser use. The results show that for comprehension, children do not reveal adult-level sensitivity to context, exhibiting instead over-selection of estar sentences. For production, all children over-produce the estar sentence, even after having just chosen the ser counterpart. However, in this task, the 10- to 12-year-olds do behave similarly to adults and differently from 4- to 6-year-olds, consistent with our hypothesis. Alternative construal requires exposure to entities and properties in a variety of situations; exposure that older children are more likely to exhibit. Collectively, these results (1) support the properties of estar use hypothesized to underlie the language-world-knowledge integration, and (2) delineate a potential developmental trajectory whereby mastery of the copula may not begin to manifest until 10–12 years of age, not because of any one linguistic factor but rather due to specific world-knowledge exposure constraints.